2021
DOI: 10.1007/s11104-021-05067-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation, translocation, and toxicity of arsenic in barley grown in contaminated soil

Abstract: Aims Arsenic is a nonessential element for plants, however, high levels of As can inhibit plant growth. Toxicity of As is largely in uenced by its speciation in soil. The objectives of the present study were to determine fractional composition of As in soil, its accumulation in plants, and toxic effects on the morphological, anatomical, and ultrastructural levels.Methods In a model experiment, barley (Hordeum sativum) was planted in Haplic Chernozem spiked with three different concentrations of As (20, 50 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Nazir et al (2021) and Rabêlo et al (2018) described the direct effect of Cd-enriched solutions on the morphology and anatomy of roots. Arsenic also affects root morphology (Zemanová et al 2020(Zemanová et al , 2022Burachevskaya et al 2021). Zn is also associated with a reduced plant root system (Genc et al 2007, Namdjoyan et al 2017.…”
Section: Controlmentioning
confidence: 99%
“…Nazir et al (2021) and Rabêlo et al (2018) described the direct effect of Cd-enriched solutions on the morphology and anatomy of roots. Arsenic also affects root morphology (Zemanová et al 2020(Zemanová et al , 2022Burachevskaya et al 2021). Zn is also associated with a reduced plant root system (Genc et al 2007, Namdjoyan et al 2017.…”
Section: Controlmentioning
confidence: 99%
“…Our results indicated that biocrusts affect heavy metal forms in the underlying layer, compared with bare soil, with the proportion of F4 (by 4.01-8.04%) decreasing and the proportion of F2, F3 and F1 increasing, more so in F2 (3.54-6.69%). This could be because: (1) biocrust succession improves soil texture in degraded ecosystems, changing the proportion of metals bound to Fe/Mn oxides and the heavy metal distribution (Bartoli et 2) Fe/Mn oxides in the soil environment immobilise heavy metals through adsorption and co-precipitation, and the metal could react with Mn or Fe to form relatively stable compounds (Burachevskaya et al 2021, Krupadam, 2007, Zhang et al 2017).…”
Section: Effect Of Biocrusts On the Migration And Transformation Of H...mentioning
confidence: 99%
“…3). The available As and Cr increased most in the underlying mixed crust and moss crust, respectively, due to the different As and Cr solubility in the underlying of different biocrust (Burachevskaya et al 2021, Zakir et al 2008).…”
Section: Effect Of Biocrusts On the Migration And Transformation Of H...mentioning
confidence: 99%
See 1 more Smart Citation